Qinjian jieyue, aixi liangshi - kan shei chide ganjing - Ha Qiongwen,
'Be hardworking and thrifty, treasure foodstuffs - let's see who can eat neat and tidy'. Setno. 8081.15558. From the series 'Propaganda posters on "primary school pupils" behavioral standard'. See also BG E13/87-96.